Persepsi pada By stander terhadap Intensitas Bullying pada Siswa SMP - Halimah, Andi; Khumas, Asniar; Zainuddin, Kurniati (Faculty of Psychology, Universitas Gadjah Mada, 2015)
This study aimed to determine the role of bystanders on the intensity of bullying against students of junior high school in Makassar. The subjects of the study were48 students aged 11-15 years old who were bullying perpetrators. The scales used for collecting data were bystanders’ perception scale bullying intensity scale. The data were analyzed using simple regression analysis techniques. The results of the analysis showed that bystanders’ perceptions could increase the intensity of bullying with r=0,343 and significant p0,017. However, the effective contribution was 11.8%. It could be concluded that the role of people present at the scene of bullying can increase it's intensity or increase the likelihood of recurrence of it among the students. The concept of student-friendly school needs urgently to be applied. All stakeholders concerned with education and morals it the shaping of students must work together to realize this ideal.